Identifying the Dimensions and Presenting Managerial Strategies for Improving the Status of Sports Accidents in Schools - Kazemi, Seyed Vahid; Shojaei, Vahid; Hami, Mohammad (Iranian Journal of Educational Sociology, 2026)
Purpose: The present study aimed to identify the managerial dimensions affecting the occurrence of sports accidents in schools and to develop practical managerial strategies for improving prevention, supervision, crisis response, documentation, and follow-up processes related to school sports accidents. Methods and Materials:This study was conducted within the interpretive–constructivist paradigm using a qualitative descriptive–analytical approach. Data were collected through semi-structured in-depth interviews and qualitative document analysis. The human participants consisted of 29 experts, including official sports experts, lawyers, judges, school principals, and university specialists in sports management, who were selected through purposive and snowball sampling. Data collection continued until theoretical saturation was achieved. In addition, 90 legal, managerial, educational, and safety-related documents were analyzed, including regulations, safety standards, ministerial directives, accident-related procedures, and supervisory documents. Data were analyzed using thematic analysis and qualitative content analysis. MAXQDA 2022 software was used for coding, classification, and organization of qualitative data. Findings: The findings showed that weak active supervision by physical education teachers, absence of operational safety standards, non-standard sports spaces and equipment, overcrowded classes, lack of initial student health assessment, and insufficient safety education were the most influential managerial factors contributing to sports accidents in schools. The results also revealed a significant gap between the current managerial status of schools and desirable international standards in the areas of risk management, crisis management, emergency preparedness, safety documentation, and root-cause analysis. The analysis demonstrated that latent systemic conditions within higher-level educational management structures had the greatest share in the occurrence of accidents. In addition, the safety culture of most schools was found to be at an initial or emerging level, characterized by weak reporting systems, absence of safety committees, lack of organizational learning, and dominance of blame-oriented approaches. Based on the findings, a comprehensive set of managerial strategies was developed focusing on prevention, risk management, human resource empowerment, documentation systems, insurance reform, electronic accident surveillance, safety culture development, and specialized supervision. Conclusion: The study concluded that sports accidents in schools are primarily the result of systemic managerial deficiencies rather than isolated individual failures. Therefore, improving the status of school sports accidents requires the establishment of an integrated managerial framework based on preventive risk management, operational safety standards, compulsory staff training, systematic supervision, organizational learning, and accountability-oriented safety culture. Effective reduction of sports accidents depends on coordinated action among educational authorities, school administrators, teachers, parents, and health-related institutions.